2014
DOI: 10.1007/s00402-014-1990-z
|View full text |Cite
|
Sign up to set email alerts
|

Restoration of joint congruency and the glenoidal labrum after arthroscopic revision Bankart repair: a MRI match-paired analysis comparing primary Bankart repair and the uninjured labrum

Abstract: Case series.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 48 publications
2
16
0
Order By: Relevance
“…The most frequent complication was recurrent instability (19.9%; N = 56). Recurrent instability was defined as a postoperative dislocation in 4 studies [15,35,40,44], a traumatic event requiring surgical intervention in 2 studies [6,12], and a subluxation or dislocation in 2 studies [3,16]. Other common complications included osteoarthritis (6.8%; N =19), persistent postoperative apprehension (2.5%; N = 7), and traumatic fracture of the glenoid (0.4%; N = 1; Table 2).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The most frequent complication was recurrent instability (19.9%; N = 56). Recurrent instability was defined as a postoperative dislocation in 4 studies [15,35,40,44], a traumatic event requiring surgical intervention in 2 studies [6,12], and a subluxation or dislocation in 2 studies [3,16]. Other common complications included osteoarthritis (6.8%; N =19), persistent postoperative apprehension (2.5%; N = 7), and traumatic fracture of the glenoid (0.4%; N = 1; Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…Of the studies that reported a mean of anchors used, 1 study (3.9%; N = 11) reported a mean of 2.5 anchors [40]; 1 study (3.6%; N = 10) reported a mean of 2.7 (range: 2-3) anchors [15]; 1 study (11.4%; n = 32) reported a range of 3 to 5 anchors used [3]; 1 study (2.1%; [42] 19 recurrent instability Buckup et al [6] 3 re-dislocation 2 persistent apprehension Bartl et al [3] 4 recurrent instability Ryu and Ryu [40] 1 recurrent instability Barnes et al [2] 1 persistent apprehension Neri et al [35] 2 re-dislocation Stein et al [44] 1 re-dislocation 4 persistent apprehension 1 traumatic failure of the glenoid Frank et al [16] 12 recurrent instability Franceschi et al [15] 1 recurrent instability N = 6) reported a range of 3 to 6 anchors used [35]; and 1 study (2.5%; N = 7) reported a minimum of 3 anchors [20]. A total of 7 studies (N = 109) reported positioning of the anchors [3,6,15,20,35,40,44]. Of these, 2 studies (15.3%; N = 43) placed the most inferior anchor at the 4:30 o'clock position and the superior anchor at the 3:00 o'clock position [6,44].…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, postoperative external rotation deficits at 0° and 90° of abduction were identified in revision cases compared with primary arthroscopic repair cases. 47…”
Section: Resultsmentioning
confidence: 99%
“…There were 4 included studies that compared revision arthroscopic stabilization with primary arthroscopic stabilization, with variable reported outcomes. 26,31,33,47 Krueger et al 26 compared 20 revision with 20 primary arthroscopic shoulder stabilization cases and reported no significant difference in the number of recurrent postoperative dislocations, although the apprehension sign was positive in 2 of the patients in the revision group. Of note, however, the number of preoperative dislocations for the primary arthroscopic stabilization group was 8.7 versus 9.8 for the revision arthroscopic stabilization group.…”
Section: Outcomes Comparing Revision With Primary Arthroscopic Repairmentioning
confidence: 99%
See 1 more Smart Citation